Pengaruh Literasi Keuangan dan Sikap Keuangan dengan Perilaku Tata Kelola Keuangan Terhadap Kepuasan Keuangan - Wahyu Hari Prihantono (Universitas La Tansa Mashiro, 2024)
Finance Management knowledge is an important aspect of the family economy in everyday life. For this reason, households, especially the head of the family and other members must be able to manage finances properly and correctly for family economic stability in order to bring satisfaction to all family members. This research measures financial literacy influence financial management behaviour, financial attitude influence financial management behaviour. Financial literacy and financial attitudes influence financial management behaviour.Financial literacy affects financial satisfaction. Financial attitude influences financial satisfaction.Financial behaviour management influences financial satisfaction. Financial literacy, financial attitudes, and financial management behaviour influence financial satisfaction. The method used in this research is quantitative method. Financial literacy and financial attitude were studied as independent variables. Behavioural financial management becomes a mediator variable; as an independent variable but also a dependent variable. Financial satisfaction will be examined as the dependent variable. The research sample was 150 married respondents, selected using non-probability sampling. Multiple Regression Analysis measures were used to test the hypothesis. The results showed that financial attitude is the factor that most influences the variable towards financial management behaviour; also financial management behaviour is the factor that most influences the variable towards financial satisfaction. The researcher recommends that giving more attention to financial attitude and financial management behaviour is important to achieve financial satisfaction. Therefore, these research results contribute to increasing married individuals' awareness that financial satisfaction can be achieved by having good financial attitudes and behavioural management